Drivers and barriers for a modal shift from road to maritime transportation within construction logistics - Erik, Insgård; John, Skoglund (My University, 2019)
Sweden has the longest coast in the EU, and several ports spread all along the coast. Despite the amounts of suitable waterways, goods volumes are concentrated on the main sea-ports in Gothenburg and Helsingborg. In an official report, the capacity for inland waterway transport in Sweden today is described as massively under-utilized. The waterway passages around Värnern, Göta älv, and Mälaren are barely utilized, and there is no feeder-traffic between the sea-ports along the coast. In a country such as Sweden, with an outspoken goal to be at the forefront of sustainability, having close to no internal waterway utilization is a failure. In areas such as construction logistics, where the goods are usually of low value, high volume, and multiple specific shapes, waterway transportation should be feasible. There are several areas in Sweden under heavy construction at the moment. For example, the areas in and around central Gothenburg and Stockholm on Sweden's coasts are currently facing some of their largest construction reformations ever. Thus, this thesis was created to examine what prevents and what empowers a modal shift from road to maritime transportation, which led to the formulation of a purpose to investigate the feasibility of a modal shift for construction material from road to waterway transportation in Sweden by examining cases where such a modal change has been carried out or planned. Further, the thesis aims to identify barriers and drivers in these cases and make suggestions on which action could be taken in order to support a modal shift. In order to resolve this, three research questions were constructed. First and second, what drivers and what barriers are identified by literature and people in the industry, and third, what can be done to overcome the barriers identified and how to accentuate the drivers? Through a study, where interviews with stakeholders in five different cases in Sweden was conducted, the main drivers were identified as reduced emissions and congestion, the proximity of waterways, technical benefits from barges and sea vessels and finally the possibility to achieve economies of scale. Further on, the main barriers identified where: habit and prejudice, flawed national incentive systems, fees related to the utilization of maritime transportation, the requirement of extra points of transshipment, lack of knowledge, flexibility performance, high investment costs for each transport and investment costs related to infrastructure. In order to overcome barriers and accentuate drivers, the results illustrate that municipal and governmental instances require to start making higher demands, change the way they construct incentive systems and incite proactiveness. The construction companies need to start considering maritime as a viable option from the procurement phase. Knowledge among governmental and municipal employees was also identified as a barrier. Increased awareness of the benefits of maritime transportation would supposedly lead to higher investments in infrastructure from different governmental instances and thus reduce the infrastructural barrier.